2019
DOI: 10.1103/physrevlett.123.217201
|View full text |Cite|
|
Sign up to set email alerts
|

Fast Domain Wall Motion Governed by Topology and Œrsted Fields in Cylindrical Magnetic Nanowires

Abstract: While the usual approach to tailor the behavior of condensed matter and nanosized systems is the choice of material or finite-size or interfacial effects, topology alone may be the key. In the context of the motion of magnetic domain-walls (DWs), known to suffer from dynamic instabilities with low mobilities, we report unprecedented velocities > 600 m/s for DWs driven by spin-transfer torques in cylindrical nanowires made of a standard ferromagnetic material. The reason is the robust stabilization of a DW type… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
61
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(65 citation statements)
references
References 45 publications
4
61
0
Order By: Relevance
“…[ 5–12 ] Indeed, first experimental realizations of cylindrical magnetic nanowires have led to the observation of new domain wall structures containing magnetic singularities, high domain wall velocities, and topological transformations, demonstrating the rich physics that can appear in these higher dimensional magnetic nanostructures. [ 13–15 ]…”
Section: Introductionmentioning
confidence: 99%
“…[ 5–12 ] Indeed, first experimental realizations of cylindrical magnetic nanowires have led to the observation of new domain wall structures containing magnetic singularities, high domain wall velocities, and topological transformations, demonstrating the rich physics that can appear in these higher dimensional magnetic nanostructures. [ 13–15 ]…”
Section: Introductionmentioning
confidence: 99%
“…As is often the case, there is not a single best methodology but rather, upon deciding upon a geometry, one should consider the strengths and weaknesses of individual approaches. For example, it is very clear that electrodeposition into anodised alumina or ion track etched templates is very well suited to producing very pure, cylindrical magnetic nanowires, with very smooth sidewalls and there is little doubt that this powerful methodology will continue to be exploited in order to explore the physics of ultrafast domain walls [34] and eventually spin-Cherenkov physics. Recent work has also shown that for the case of anodised alumina templates, more complex connected nanowire structures can be made [89] suggesting that this methodology may also allow the realization of complex 3D nanowire lattices.…”
Section: Discussionmentioning
confidence: 99%
“…Today, 3D Nanomagnetism has come of age [32], providing the potential to host a plethora of new physics including spin textures locked by topological protection [33], ultrafast domain wall motion [34], controlled spin-wave emission [35,36], magnetochiral effects [32] and curvature-driven energies that produce new effective interactions [37][38][39][40]. A thorough investigation of these phenomena now demand new fabrication techniques that enable controlled sub-100 nm growth of magnetic materials in three-dimensions.…”
Section: Introductionmentioning
confidence: 99%
“…Each segment's magnetization direction reverses either by coherent rotation or by nucleation and propagation of a DW, depending on their composition (e.g., defining its magnetocrystalline anisotropy) and length [111], [204]. This reversal can be driven by magnetic fields [36], [37], electric currents [43], [205] or a combination of both [44] with DWs possibly transforming during motion [206]. In particular, the experiments with cobalt and nickel-based NWs of diameters around 90 nm have resulted in current-induced DW velocities up to 600 m/s [44], [205].…”
Section: A Non-volatile Data Storagementioning
confidence: 99%
“…• Arrays of NWs have been used as electromagnetic pulse detectors [3], microwaves circulators or phase shifters [29]- [32] at 10 -40 GHz frequencies. • When isolated, effects like giant magneto-resistance (GMR) [33]- [35], domain wall (DW) pinning [36]- [38] and spin transfer torque (STT) [39]- [41] are exploited mainly for prospective memory applications [42]- [45] employing nanoseconds (GHz) pulses. 1000 kHz (1 MHz) to the GHz regime.…”
Section: Introductionmentioning
confidence: 99%